The Impact Of The E-Commerce Commercial Jingle On Customer Attitude Among Generation Z Audiences - Muhammad Aqshel Revinzky Nizar; Rizky Ramadhan; Kamal, Irsyad (CV Putra Publisher, 2025)
The COVID-19 pandemic caused significant disruption to Indonesia’s economy, severely affecting traditional commerce while accelerating the growth of e-commerce. Shopee, as the market leader, leveraged various marketing strategies, including its Shopee COD (Cash on Delivery) commercial jingle, to strengthen brand awareness and attract users. This study examines the quality of the Shopee COD commercial jingle, analyzes Generation Z customers’ attitudes toward it, and evaluates its influence on these attitudes. Using a quantitative, causal associative approach, data were collected via an online survey of 125 Generation Z respondents who had heard the jingle and used the Shopee application. The study adopts a five-dimensional jingle evaluation model (memorability, meaningfulness, likability, adaptability, protectability) and the ABC Model of Attitudes (affective, behavioral, cognitive) to analyze the relationship between jingle quality and customer attitudes. Results show a significant positive correlation between jingle quality and customer attitude, with jingle quality explaining 42% of the variance in attitudes.